The Influence Of Service Quality And Price On Customer Loyalty Through Customer Satisfaction As Mediation In Customers Of PT. Usaha Tangguh Mandiri Bandung - Bella Gitarisa; Yenny Maya Dora (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to evaluate the influence of service quality and price on customer loyalty, with customer satisfaction as a mediating variable, at PT Usaha Tangguh Mandiri, a food distribution company. A quantitative approach was employed in this research, with data collected using a 5-point Likert scale questionnaire. The sample consisted of 72 respondents who are active customers of the company. Data analysis was conducted using the Partial Least Squares (PLS) method with the assistance of SmartPLS 4.0 software. The analysis results indicate that price has a significant impact on customer satisfaction, while customer satisfaction positively influences customer loyalty. Additionally, service quality was found to have a direct significant effect on customer loyalty. However, the study did not find a significant influence of service quality on customer satisfaction, price on customer loyalty, or the mediating effect of customer satisfaction in the relationship between service quality and price on customer loyalty. These findings provide valuable insights for the company in formulating more effective marketing strategies to enhance customer loyalty, focusing on elements that have a significant impact.